2010
DOI: 10.1086/652149
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Risk for Clinically Significant Drug Interactions among HIV‐Infected Patients Receiving Antiretroviral Therapy

Abstract: We assessed the risk of clinically significant drug interactions in patients receiving antiretrovirals, and their recognition by physicians. Clinically significant drug interactions were recorded in 27% of 159 patients, with 15% of interactions potentially lowering antiretroviral concentrations. Risk of clinically significant drug interactions was significantly related to receipt of protease inhibitors. Only 36% of clinically significant drug interactions were correctly identified by physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 7 publications
7
84
2
2
Order By: Relevance
“…Despite the growing number of clinical trials assessing novel TB drugs, there is still not credible alternative to rifampicin-based therapy, and this remained the predominant cause of CSDIs in our study. Also TB is the first co-infected disease during the AIDS in Côte d'Ivoire [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the growing number of clinical trials assessing novel TB drugs, there is still not credible alternative to rifampicin-based therapy, and this remained the predominant cause of CSDIs in our study. Also TB is the first co-infected disease during the AIDS in Côte d'Ivoire [12].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we screened first, 560 consecutive patients According to the national Ivorian 2013 guidelines, first-line antiretroviral were defined as Tenofovir (TDF) or zidovudine (ZDV) plus lamivudine (3TC) plus nevirapine (NVP) or Efavirenz (EFV), and substitution with Tenofovir (TDF), abacavir (ABC) or didanosine (ddI) was allowed for toxicity. [12]. All the coprescribed drug pairs were screened for potential for DDSI using the Liverpool HIV Pharmacology Group website (www.hiv-druginteractions.org) [13].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Oleh karena itu, sebelum memulai terapi, perlu ditanyakan mengenai riwayat penggunaan obat-obatan agar terapi yang diberikan aman, akurat dan tepat waktu. Perlu juga dievaluasi mengenai gangguan kognitif pada pasien yang dapat berpengaruh terhadap kepatuhan berobat.…”
Section: Masalah Terkait Terapi Antiretroviralunclassified
“…So-called 'polypharmacy', usually defined as five or more medications, has been linked to decreased adherence, increased adverse drug reactions, more hospitalizations and an increase in mortality [4]. Evans et al recently found that 27% of HIV-infected patients had a clinically significant drug interaction between their highly active antiretroviral therapy (HAART) and another agent [5].We performed an audit to quantify polypharmacy in our large UK HIV-infected cohort using an HIV clinical care database. Using our HIV clinic database for patients attending in the year prior to 4 October 2013, we extracted demographics, antiretroviral regimen and list of all other medications.…”
mentioning
confidence: 99%